Design and optimization of an umbrella-type shield based on 3D CFD simulation technology - Li, Longfei (Strojniški vestnik, 2023)
Mechanical shields can effectively alleviate the problems of low pesticide utilization and severe environmental pollution. This manuscript uses a computational fluid dynamics (CFD) method to investigate the anti-drift mechanism of mechanical shields, study the airflow forms around them, and establish an accurate simulation model. The aerodynamic characteristics of six shields were studied, and their anti-drift effect was compared. Then, the size and working parameters were optimized using the response surface methodology (RSM). Mechanical shields can significantly improve the fog droplet deposition rate (DR) compared with the conventional spray method (no shield), among which the umbrella-type shield has the best effect; optimizing the size and selecting suitable working parameters can increase the DR to 77.31 %. The field trial showed that the DR of the conventional spray method was reduced by 31.9 % at 5 m/s compared with 3 m/s, while the DR of the shield spray method was reduced by only 3.6 % at 5 m/s compared with 3 m/s, which proved the excellent performance of the mechanical shields. The field trial results were consistent with the CFD simulation, and the relative deviation of the DR between the two was within 4 %, so the accuracy and reliability of the CFD simulation model were proved.
Keywords: aerodinamične lastnosti; anti-drift; CFD simulation; mechanical shield; mehanizem za preprečevanje drifta; mehanski ščit; metoda odzivnih površin; računalniška dinamika fluidov; stopnja odlaganja kapljic